Structural, microstructural and dielectric characterizations of (Bi 0. 5 Na 0. 5)TiO3based lead-free ferroelectric ceramics - Moya, B. R. [UNESP]; Silva, A. C.; Peláiz-Barranco, A.; Guerra, J. D.S. (World Scientific Publishing, 2021)
(1-x)Bi0.5Na0.5TiO3-xBaTiO3lead-free ceramics have been obtained from the conventional solid-state reaction sintering method. The structural properties were investigated from X-ray diffraction and Raman spectroscopy techniques. Results revealed well-crystallized ceramic samples with perovskite structure. Microstructural properties, obtained from scanning electron microscopy measurements, have shown high density with very low porosity level. The dielectric response, analyzed as a function of the temperature and several frequencies, showed very broad peaks with a strong frequency dependence of the temperature for the maximum dielectric permittivity for the modified system. Results were analyzed considering the influence of the BaTiO3 content on the studied physical properties.
Keywords: BNT; dielectric response; Lead-free; Raman spectroscopy